1058. Prognostic Biomarkers for Persistent Bacteremia and Mortality in Complicated S. aureus Bloodstream Infection. (26th November 2018) - Cao, Yi; Guimaraes, Alessander; Hong, Kyu; Mayba, Oleg; Peck, Melicent; Gutierrez, Johnny; Ruffin, Felicia; Carrasco-Triguero, Montserrat; Dinoso, Jason; Clemenzi-Allen, A Asa; Koss, Catherine; Maskarinec, Stacey A; et al.
Abstract: Background: Staphylococcus aureus is a leading cause of bacteremia, yet there remains a significant knowledge gap in the identification of relevant biomarkers that predict clinical outcomes in patients with S. aureus bacteremia. Heterogeneity in the host response to invasive S. aureus infection suggests that specific biomarker signatures could be utilized to differentiate patients prone to severe disease, thereby facilitating earlier implementation of more aggressive therapies. To further elucidate the inflammatory correlates of poor clinical outcomes in patients with S. aureus bacteremia, we evaluated the association between a panel of blood proteins at initial presentation of bacteremia and disease severity outcomes. Methods: We conducted an observational study ( n = 32) to evaluate the prognostic value of circulating protein biomarkers for mortality and persistent bacteremia in patients with S. aureus bloodstream infections. A case–control study of 124 patients with complicated confirmed S. aureus bloodstream infections was used to validate our findings in the observational study. Results: We identified 13 candidate proteins that were correlated with mortality and persistent bacteremia by multiple comparisons. Further statistical modeling identified IL-8 and CCL2 as the strongest individual predictors of mortality, with the combination of these biomarkers having the best power to classify fatal outcome. Baseline IL-17A levels were elevated in patients with persistent bacteremia, endovascular and metastatic tissue infections. Conclusion: The results demonstrate the potential utility of selected biomarkers to distinguish patients with the highest risk for treatment failure and bacteremia-related complications, providing a valuable tool for clinicians in the management of S. aureus bacteremia. Additionally, these biomarkers could identify patients with the greatest potential to benefit from novel therapies in clinical trials. Disclosures: All authors: No reported disclosures.